Contraceptive Knowledge among Females and Males Receiving Medication Treatment for Opioid Use Disorder Compared to Those Seeking Primary Care. (3rd October 2020) - Melbostad, Heidi S.; Badger, Gary J.; Rey, Catalina N.; MacAfee, Lauren K.; Dougherty, Anne K.; Sigmon, Stacey C.; Heil, Sarah H.
Abstract: Background: Rates of unintended pregnancy among women receiving medication treatment for opioid use disorder (mOUD) are high, likely due in part to low rates of contraceptive use. Lack of knowledge about contraception may be contributing to inadequate contraceptive use. Objectives: To compare contraceptive knowledge among women and men receiving mOUD relative to a comparison group seeking primary care. Methods: We surveyed 332 reproductive-age women and men receiving mOUD or primary care with the recently validated 25-item Contraceptive Knowledge Assessment. We examined overall differences between patient groups and between females and males using two-way analyses of variance; individual item differences were tested using logistic regression. Results: The mean percent of total correct responses was lower among individuals receiving mOUD ( n  = 167) relative to the comparison group ( n  = 165), 47.7% vs. 53.8%, respectively ( p < .001), and higher among females ( n  = 169) relative to males ( n  = 163), 56.1% vs. 45.2%, respectively ( p < .001). Individual item analyses revealed patient group and sex differences primarily in the areas of contraceptive efficacy, attributes of contraceptive methods, and fertility awareness. Conclusion: While there were modest differences between patient groups and sexes, the results suggest a deficit in contraceptive knowledge across all groups. Substance use disorder treatment clinics could be an opportunistic setting in which to provide accurate information about contraception to patients with OUD and other substance use disorders.